Mechanisms of Bactericidal Action of Cinnamaldehyde against Listeria monocytogenes and of Eugenol against L. monocytogenes and Lactobacillus sakei - Gill, Alexander O. (American Society for Microbiology, 2004)
The spice oil components eugenol and cinnamaldehyde possess activity against both gram-positive and gram-negative bacteria, but the mechanisms of action remain obscure. In broth media at 20°C, 5 mM eugenol or 30 mM cinnamaldehyde was bactericidal (>1-log reduction in the number of CFU per milliliter in 1 h) to Listeria monocytogenes. At a concentration of 6 mM eugenol was bactericidal to Lactobacillus sakei, but treatment with 0.5 M cinnamaldehyde had no significant effect. To investigate the role of interference with energy generation in the mechanism of action, the cellular and extracellular ATP levels of cells in HEPES buffer at 20°C were measured. Treatment of nonenergized L. monocytogenes with 5 mM eugenol, 40 mM cinnamaldehyde, or 10 μM carbonyl cyanide m-chlorophenylhydrazone (CCCP) for 5 min prevented an increase in the cellular ATP concentration upon addition of glucose. Treatment of energized L. monocytogenes with 40 mM cinnamaldehyde or 10 μM CCCP caused a rapid decline in cellular ATP levels, but 5 mM eugenol had no effect on cellular ATP. Treatment of L. sakei with 10 mM eugenol prevented ATP generation by nonenergized cells and had no effect on the cellular ATP of energized cells. CCCP at a concentration of 100 μM had no significant effect on the cellular ATP of L. sakei. No significant changes in extracellular ATP were observed. Due to their rapidity, effects on energy generation clearly play a major role in the activity of eugenol and cinnamaldehyde at bactericidal concentrations. The possible mechanisms of inhibition of energy generation are inhibition of glucose uptake or utilization of glucose and effects on membrane permeability.